Problematika Koperasi Merah Putih di Nagari Tanjung Beringin Menurut Perspektif Fiqh Siyasah Tanfiziyah - Ezima Putri; Busyro (AHKAM, 2026)
The establishment of Koperasi Merah Putih in Nagari Tanjung Beringin represents a government effort to strengthen the village-based community economy. However, its implementation continues to face various institutional, administrative, and technical constraints that affect the effectiveness of cooperative management. This study aimed to analyze the implementation of Koperasi Merah Putih in Nagari Tanjung Beringin and examine the problems that have emerged from the perspective of Fikih Siyasah Tanfiziyah. The study employed a qualitative approach with a descriptive design. Primary data were obtained through interviews with cooperative managers and members, the nagari government, religious leaders, customary leaders, and community members, whereas secondary data were derived from laws and regulations, books, journals, and supporting documents. Data were collected through observation, interviews, and documentation and were subsequently analyzed qualitatively. The results showed that Koperasi Merah Putih was established through a Special Village Deliberation as an implementation of government policy to improve community welfare. Despite receiving government support and positive responses from the community, the cooperative continued to face limitations in capital, facilities and infrastructure, human resource capacity, and administrative capabilities. From the perspective of Fikih Siyasah Tanfiziyah, the implementation of the cooperative reflected the principles of trustworthiness, deliberation, justice, and public welfare, but remained suboptimal in terms of governance and supervision. These findings confirm that the successful implementation of Koperasi Merah Putih requires institutional strengthening, enhancement of management capacity, and continuous government assistance. This study contributes to the development of Fikih Siyasah Tanfiziyah studies in the implementation of village economic policies and provides practical implications for local governments and cooperative managers in realizing professional, transparent, and sustainable governance.